Effects of Nyaope of families with a family member that is addicted to the drug Nyaope - Nkosi, Hlengiwe Setty (My University, 2017)
The use of Nyaope amongst South Africans has risen dramatically since it first appeared on the streets. Real concerns have been voiced about the negative effects this street drug has had on communities in South Africa. Some townships in South Africa claim to have been ruined by Nyaope. There were various reasons to conduct the study; firstly families experience many negative effects associated with having an addicted member in their family; for example the addition of family members on nyaope causes disharmony and conflicts within families of the addicted individuals. Moreover families experience despair, shame and helplessness; nevertheless families also feel intimidated by the addicted person due to their undesirable behaviour and therefore find it hard to cope within the family and within the community. The primary aim for this study is to explore the effects and challenges of nyaope on families. This study adopted the qualitative research design to gather information/data. The type of qualitative design that was used in this study was the case study where the researcher focus on different cases related to the topic being researched. Moreover the method that was used to gather information was face-to-face interviews where the research tool was the semi-structure interview schedule. Findings were analysed using the thematic analysis. Anticipated value of findings for the study was that it is challenging in a micro, meso and macro level to live with persons using the drug nyaope, hence there are different and/or various negative effects in all three dimensions. The findings of the study was there are various challenges experienced by families that have a family member who is addicted to the drug nyaope and those involve emotional distress and physical manifestation of that stress, there is stigma attached to having a family member that is addicted to nyaope and there are also financial challenges experienced by families that have a family member that is addicted. Moreover there are various resources that were identified in the course of this study that families normaly resort to in dealing with the situation of having a family member that is addicted to nyaope. However every family deals with the problem of having a family member that is addicted to nyaope in a different way that are suitable or best for the as a unit.
A research report submitted to the Department of Social Work, School of Human and Community Development, University of the Witwatersrand In partial fulfilment of the requirements for the Degree of Bachelor of Social Work